Signaling Unobservable Product Quality through a Brand Ally - Rao, Akshay R.; Qu, Lu; Ruekert, Robert W. (Journal of Marketing Research, 1999)
In this article, the authors examine the circumstances in which brand names convey information about unobservable quality. They argue that a brand name can convey unobservable quality credibly when false claims will result in intolerable economic losses. These losses can occur for two reasons: (1) losses of reputation or sunk investments and (2) losses of future profits that occur whether or not the brand has a reputation. The authors test this assertion in the context of the emerging practice of brand alliances. Results from several studies are supportive of the premise and suggest that, when evaluating a product that has an important unobservable attribute, consumers’ quality perceptions are enhanced when a brand is allied with a second brand that is perceived to be vulnerable to consumer sanctions. The authors discuss the theoretical and substantive implications for the area of brand management.